An assessment of ultrasonic pulse velocity measurement as a viable proxy for weathering in South African gabbro tombstones. Issue 1 (2nd January 2022) - Loubser, Michael
ABSTRACT: Ultrasonic pulse velocity (UPV) measurement has previously been determined to be a good proxy for rock weathering intensity. As such, it has the potential to be useful for the establishment of relative weathering rates in culturally sensitive artefacts such as tombstones. This is the first study that makes use of an ultrasonic proxy in this manner to be carried out in South Africa, where many tombstones are constructed from locally produced gabbro stone. However, the delimitations of ultrasonic equipment have not been appropriately established for use on this particular lithology. This study investigates the relationship between UPV and the amount of time various tombstones have spent in situ at Cullinan Main Cemetery in South Africa, with the aim of determining if UPV can accurately be used to assess relative weathering rates for the tombstones there. Ultrasonic measurements were taken with two different transducer packages on 34 tombstones that had remained in the cemetery for between 15 and 100 years. The results show that there is a measurable, statistically significant positive relationship between inscription age and ultrasonic pulse velocity (UPV), supporting the hypothesis that UPV is a valid proxy for rock weathering with respect to South African gabbro tombstones.